2010
DOI: 10.2754/avb201079s9s021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vegetable Oil Fortified Feeds on the Content of Fatty Acids in Breast and Thigh Muscles in Broiler Chickens

Abstract: The main objective of this work was to compare the effect of six vegetable oils added to feeding mixtures that were administered to broiler chickens on the content of major fatty acids in chicken meat. The experiment started with 90 one-day-old Ross 308 meat hybrid male chickens that were divided into six groups. Chickens were fed complete feeding mixtures for the prefattening (BR1), fattening (BR2), and post-fattening (BR3) of broiler chickens. The BR1 feeding mixture was administered to chickens aged 1-10 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…If broiler feed is supplemented only with sunflower oil, portion of αLNA is lower than in case of linseed oil supplementation. Krejčí-Treu et al (2010) reported that feeding broilers with diets enriched with sunflower oil resulted in the content of αLNA in lipids being 1.04 g/100 g of lipids, whereas in the case of dietary supplementation with linseed oil that content was significantly higher, being 7.47 g/100 g of lipids in thigh muscle. Yaroshenko et al (2004) determined significantly lower concentration of MDA in breasts and thigh muscles in an experimental group of broilers that were fed diets supplemented with selenium (0.4-0.8 mg/kg) compared to control broilers that consumed standard diet.…”
Section: Discussionmentioning
confidence: 99%
“…If broiler feed is supplemented only with sunflower oil, portion of αLNA is lower than in case of linseed oil supplementation. Krejčí-Treu et al (2010) reported that feeding broilers with diets enriched with sunflower oil resulted in the content of αLNA in lipids being 1.04 g/100 g of lipids, whereas in the case of dietary supplementation with linseed oil that content was significantly higher, being 7.47 g/100 g of lipids in thigh muscle. Yaroshenko et al (2004) determined significantly lower concentration of MDA in breasts and thigh muscles in an experimental group of broilers that were fed diets supplemented with selenium (0.4-0.8 mg/kg) compared to control broilers that consumed standard diet.…”
Section: Discussionmentioning
confidence: 99%
“…In poultry, it is common that dietary fat has a great influence on fatty acid profiles of poultry meat [5,6]. Polyunsaturated fatty acids (PUFA) intake including n-3 and n-6 fatty acids have beneficial effects on both animal and consumer health.…”
Section: Introductionmentioning
confidence: 99%
“…Not only the variety but also the sowing interval may affect the flax oil composition, as was found by Endes et al (2012). According to recommendations by Krejčí-Treu et al (2010), flax, rape and sunflower seed oils were the most suitable oils with the SFA content less than 10%; rapeseed oil had the best concentrations of n-6 FA (17.3%) and n-3 FA (6.6%). The n-3/n-6 FA ratio is 0.38 in rapeseed oil which is higher than recommended by Straková et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations for human diet are as follows: fat should represent 15-30% of the overall energy intake, of which saturated fatty acids should account for less than 10%, polyunsaturated fatty acids for 6-10%, n-6 for 5-8%, n-3 for 1-2%, and trans fatty acids for less than 1% (Krejčí-Treu et al 2010). Special emphasis is laid on sufficient intake of n-3 FA and mutual proportion of n-3 FA:n-6 FA in the diet.…”
mentioning
confidence: 99%
See 1 more Smart Citation